Africa and Indonesia reconsidered - Nurse, G. T. (International Library of African Music, 1999)
In 1964 the late Dr A. M. Jones published a book entitled Africa and Indonesia: the evidence of the xylophone and other musical and cultural factors, in which he set out a quantity of data which he considered in sum to constitute evidence for cultural and social contact between Africa and Indonesia at a period well before the heyday of Portuguese exploration. Not all of his points had to do with music, but to his case music was central and pre-eminent and the musical and musicological arguments he presented were detailed enough to carry a great deal of conviction.
Keywords: African Music